MANAJEMEN STRATEGI LABELING PRODUK OLAHAN MAKANAN RINGAN PADA USAHA KECIL MENENGAH (UMKM) DI DESA RANTAU PURI - Sophia, Sophia; Armando, Reno; Tukidi, Tukidi (Bersama : Jurnal Pengabdian Kepada Masyarakat, 2024)
Good and attractive product packaging and labeling techniques are needed to support a food product. Not all producers or food business actors such as as Micro, Small and Medium Enterprises (MSMEs) can apply modern packaging techniques. Until now, product packaging is still a problem for food business actors, especially Micro, Small and Medium Enterprises. Problems about product packaging and labels are sometimes an obstacle for the development or progress of a food processing business. The problem that occurs in snack food business actors in Rantau Puri Village is that people do not know how to package snack products in an attractive way so that buyers can easily identify them. The purpose of community service activities in Rantau Puri Village is through the transfer of knowledge and technology of snack packaging so that it is easily recognized by the market and to increase the number of processed snack products that can be produced and marketed. Packaging and labeling in the context of marketing food products is very important to do. Activities in this community service are in the form of mentoring, counseling and training for joint business groups and individual businesses specifically for micro-enterprises in the field of snack food processing, such as Balado sweet potato chips, banana chips, peanut brittle and fish crackers in Pematang Gajah Village, Jambi District Outside the City, Muaro Regency. Jambi. In addition to functioning as a means of protecting the product, packaging also increases the attractiveness of consumers to buy a certain product. Serving snacks that are packaged in clean, nice, waterproof containers will certainly increase sales. In addition to the most important thing from this packaging activity is labeling. Labeling serves as the identity of a product so that consumers can choose the product correctly and appropriately. Keywords: Packaging Produt, Product Labeling, and Snacks.